Development of basic physiological groups of soil microflora at the using of Trichoderma and Gaupsin for growing cucumbers - Balvas-Gremyakova, K.M.; Tkalenko, A.N.; Kotvitska, L.M.; Boroday, V.V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of microbiological studies of soil for growing cucumbers using biological preparation of Trichoderm and Gaupsin are showed. It was found that the using of biological products contributed to the formation of different levels of soil biological activity, it was reflected in the change of the growth of microorganisms of different ecological trophic groups, the increase in the processes of transformation of organic and inorganic compounds.